A study on Sarawak Sago Industry : the marketing strategy / Idris Hj Ibrahim - Hj Ibrahim, Idris (1997)
Sago starch has been an economically important crop for Sarawak. It comes in the processed form of sago flour classified into the food grade and the relatively inferior industrial grade. Currently, the export of sago starch is the fourth highest revenue earner of Sarawak in the agricultural sector after oil palm, pepper and cocoa. With an annual world market demand of about 20 million tons of starch, sago only contribute a mere 3% with majority of the share is taken up by corn, potato and tapioca starches.